Taxonomy of the Phyllotis osilae species group in Argentina; the status of the “Rata de los nogales” (Phyllotis nogalaris Thomas, 1921; Rodentia: Cricetidae) - Jayat, J. Pablo; Ortiz, Pablo E.; D’elía, Guillermo (Zootaxa, 2016)
The taxonomic status of populations of the genus Phyllotis from northwestern Argentina (NWA) has undergone recent changes, with the addition of two species (P. alisosiensis and P. anitae) to the traditionally recognized forms (P. caprinus, P. xanthopygus, and P. osilae). Three of these species (P. anitae, P. osilae, and P. alisosiensis) were included within the Phyllotis osilae species group. Most authors recognized three subspecies of P. osilae for NWA: P. osilae osilae, P. o. nogalaris, and P. o. tucumanus. Morphological, morphometric, and molecular studies based on recently collected specimens suggest that current classification does not reflect the diversity of this group in NWA, revealing the need of some taxonomic reallocations and new distributional delimitations. Here we propose that P. nogalaris must be recognized as a valid species and the restriction of P. osilae to southern Peru and central Bolivia. Following our results, we expect an outstanding improvement in the taxonomic knowledge of the Phyllotis osilae species group in the coming years.